Gender equality in Nepal: How is it going as a goal of SDG? - Pokharel, Bandana (Journey for Sustainable Development and Peace Journal, 2024)
This paper explores the relationship between gender equality and the Sustainable Development Goals (SDGs) in the context of Nepal. The paper aims to shed light on the multifaceted challenges faced by Nepalese society in achieving gender parity and sustainable development simultaneously. It begins by providing a comprehensive overview of the status of gender equality in Nepal, examining key indicators such as education, employment, healthcare, and political participation. The study then delves into the intersectionality of gender issues and the SDGs, analyzing how achieving gender equality contributes to the accomplishment of broader development objectives. It investigates the interlinkages between gender-specific targets outlined in the SDGs and their impact on poverty reduction, economic growth, environmental sustainability, and social inclusion in the Nepalese context. It uses a method of exploring and consolidating secondary sources to discuss how SDGs impact social, economic, and environmental aspects, emphasizing the significance of gender equality for human well-being and justice. It stresses the necessity of unified efforts to address gender gaps, empower women, and involve them in decision-making. The findings and recommendations presented in this paper contribute to ongoing discussions on gender equality and sustainable development in Nepal, providing insights for policymakers, researchers, and practitioners alike.